2021
DOI: 10.1016/j.addbeh.2020.106692
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of death among SARS-CoV-2 positive veterans: The contribution of lifetime tobacco use

Abstract: Highlights Examined factors that contribute to likelihood of death among veterans with COVID-19. Retrospective chart reviews were conducted on 440 SARS-CoV-2 positive veterans. Older age and male gender increased risk of death. Further, immunodeficiency, endocrine, and pulmonary diseases increased risk of death. Notably, lifetime tobacco use predicted veteran mortality above and beyond these variables.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…We excluded the percentage of smokers in the county as the research on smoking and COVID-19 outcomes is mixed (see e.g.,Raines et al 2020; Adrish 2020; Para-Bracamonte 2020) and some have even found an inverse association between smoking and COVID 19(Iyanda et al 2020), which is thought to be related to colliders bias(Griffith et al 2020). 3 State-by-week and housing insecurity-by-week fixed effects are not reported.…”
mentioning
confidence: 99%
“…We excluded the percentage of smokers in the county as the research on smoking and COVID-19 outcomes is mixed (see e.g.,Raines et al 2020; Adrish 2020; Para-Bracamonte 2020) and some have even found an inverse association between smoking and COVID 19(Iyanda et al 2020), which is thought to be related to colliders bias(Griffith et al 2020). 3 State-by-week and housing insecurity-by-week fixed effects are not reported.…”
mentioning
confidence: 99%
“…Amanda et al found a positive relation between lifetime tobacco use and the rate of testing positive for SARS-CoV-2, as well as the likelihood of COVID-19 mortality. 22 Social and behavioral risk factors are common in veterans; however, surprisingly in veterans with COVID-19, housing issues, financial difficulty, alcohol use, and substance use were not associated with higher mortality. 23 …”
Section: Resultsmentioning
confidence: 96%
“…Further, as previously noted, pre-existing medical conditions such as lung, kidney, and cardiovascular diseases were not associated with delirium when accounting for other medical variables. This is somewhat surprising given that these conditions are frequently associated with more severe illness in the context of COVID-19 ( Raines et al, 2021 ); however, delirium is only one of many possible illness severity indicators. Lastly, marital status was not associated with delirium which might suggest that previously established protective factors, such as social support, were of little relevance during a pandemic where family were not allowed at bedside ( Do et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%